The Influence Of Service Quality And Promotion On Customer Satisfaction (Survey On Maxim Online Transportation Customers In Tasikmalaya City): - Adawiyah, Dian Tri; Askolani; Patimah, Titin (Utami Publisher, 2025)
This research aims to determine the influence of service quality and promotion on customer satisfaction (Survey of Maxim Online Transportation Customers in Tasikmalaya City). The method used in this research is quantitative through a survey approach. In this research, the samples taken were 100 Maxim Online Transportation Customers in Tasikmalaya City. The data used is primary and secondary data. The analytical tool used in this research is multiple linear regression using SPSS 26.0. The research results show that the service quality obtained from Maxim Online Transportation Customers in Tasikmalaya City has good criteria. Promotions for Maxim Online Transportation Customer products in Tasikmalaya City have good assessment criteria, Customer Satisfaction for Maxim Online Transportation Customers in Tasikmalaya City has good criteria. Together, Service Quality and Promotion have a significant influence on Customer Satisfaction. Partially, Service Quality has a significant influence on Customer Satisfaction. Partially Promotion has a positive and significant effect on Customer Satisfaction.